Moulding the Corporate Social Responsibility Agenda in Singapore - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2008)
No longer the domain of big companies where it was equated with philanthropy, corporate social responsibility (CSR) is now part of the triple bottom-line. Businesses, big and small, must take into account the interests of `stakeholders’, not just `shareholders’. Singapore Management University law professor Eugene Tan is author of a working paper on the state of CSR in Singapore. According to Tan, the state has taken on the role of promoter and practitioner of CSR, a logical development in view of the dominant role of the government in the local economy.